THE EFFECT OF INFORMATION TECHNOLOGY BASED FLIPPED CLASSROOM LEARNING MODEL ON THE CREATIVITY AND LEARNING OUTCOMES OF CIVIC EDUCATION AT GRADE IV OF SDN BLIGO - Ninik Fatmawati; Yatim Riyanto; Rr Nanik Setyowati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to determine the effect of information technology-based flipped classroom learning model on creativity and learning outcomes for grade four Civics at SDN Bligo. This research was an experimental research with a pretest post test control group design. The subjects of this study were fourth grade students of SDN Bligo Sidoarjo. Data collection techniques were through creativity test and learning outcomes tests. Furthermore, the data were tested by using validity and reliability tests, while the learning tools were tested by expert validation. The requirements of the data analysis test were normality test and homogeneity test. The analytical technique used was t test. In this case, the t-test was carried out twice, first, to determine the initial conditions (pretest) of the experimental group and control group and second, to determine the condition after being given treatment (posttest). The results showed that (1) there was an effect of the information technology-based flipped classroom learning model on the creativity of students on Civics education at the fourth grade of elementary schools; (2) there was an effect of the information technology-based flipped classroom learning model on students’ learning outcomes on the Civics lesson at the fourth grade of elementary school. In short, this learning model could be used as a solution for learning from home or online learning that students were currently doing due to the impact of the COVID-19 pandemic.